2022
DOI: 10.1111/jfbc.14301
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharide promotes proliferation of human melanocytes via activating the Nrf2/p62 signaling pathway by inducing autophagy in vitro

Abstract: Vitiligo is a skin disease characterized by lack of functional melanocytes. Lycium barbarum polysaccharide (LBP) has been demonstrated to preserve keratinocytes and fibroblasts against oxidative stress. This study aimed to explore the efficacy and underlying mechanisms of LBP on autophagy in H 2 O 2 -damaged human melanocytes. Cellular viability was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoli um bromide assay and annexin V-fluorescein isothiocyanate/propidium iodide double staining. Reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that LBP has a great potential in the treatment of various physiological and pathological processes. 51,52 LBP is composed of a complex mixture of polysaccharides and proteoglycans. Its main constituents include arabinose, glucose, galactose, mannose, rhamnose, xylose, and galacturonic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that LBP has a great potential in the treatment of various physiological and pathological processes. 51,52 LBP is composed of a complex mixture of polysaccharides and proteoglycans. Its main constituents include arabinose, glucose, galactose, mannose, rhamnose, xylose, and galacturonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LBP has a great potential in the treatment of various physiological and pathological processes 51,52 . LBP is composed of a complex mixture of polysaccharides and proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds can protect melanocytes against oxidative stress through NRF2 activation (Table 1). Melatonin and its metabolites (6-hydroxymelatonin, N1-acetyl-N2-formyl-5-methoxykynuramine, N-acetylserotonin, and 5-methoxytryptamine) [101], vitamins (folic acid [102], methylcobalamin [103], and vitamin D [104]), natural compounds (4-octyl itaconate [105], ginsenoside Rk1 [106], Cistanche deserticola polysaccharides [107], glycyrrhizin [108], Lycium barbarum polysaccharides [109], paeoniflorin [110], 6-shogaol [111], paeonol [112], afzelin [113], apigenin [114], baicalein [115], vitexin [116], and berberine [117]), and therapeutic agents (aspirin [118], dimethyl fumarate [DMF] [94], simvastatin [29], molecular hydrogen [52], and cold atmospheric plasma [119]) are shown to protect melanocytes against oxidative damage caused by H 2 O 2 , UVB, or MBEH. DMF is the methyl ester of fumaric acid and is one of the most successful NRF2 activators.…”
Section: Nrf2 In Vitiligo Pathologymentioning
confidence: 99%